2020
DOI: 10.1108/ijchm-02-2019-0128
|View full text |Cite
|
Sign up to set email alerts
|

The scale development of organizational culture on customer delight

Abstract: Purpose The purpose of this study is to develop and validate a hospitality cultural scale for measuring the effect of organizational culture on customer delight (OCCD). Design/methodology/approach A literature review and focus group discussion were conducted to generate an initial item pool. Subsequently, three individual samples of hotel employees were identified to develop and validate the OCCD scale. Exploratory factor analysis was conducted for item purification and factor extraction, and confirmatory fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 96 publications
(132 reference statements)
2
19
0
1
Order By: Relevance
“…Over the years, the shape of the curve of KeyWord Plus accumulated growth shows performance influence, followed by keywords related to antecedents, perceptions, service climate, and job satisfaction (Figure 10). These data results confirm recent scientific production, such as culture as an antecedent of service climate [61], job satisfaction, and organizational commitment [84], and service climate and empowerment for customer service quality [85].…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…Over the years, the shape of the curve of KeyWord Plus accumulated growth shows performance influence, followed by keywords related to antecedents, perceptions, service climate, and job satisfaction (Figure 10). These data results confirm recent scientific production, such as culture as an antecedent of service climate [61], job satisfaction, and organizational commitment [84], and service climate and empowerment for customer service quality [85].…”
Section: Introductionsupporting
confidence: 86%
“…At least, culture is an antecedent of the service climate. The results showed that culture interacts with other elements, controls them, and positively impacts the service climate [61,110].…”
Section: Content Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In a follow-up study, Finn (2012) developed an analysis to distinguish customer delight from customer satisfaction and argued that customer delight results from surprising and positive levels of service performance identified by an emotion distinct from satisfaction. Only recently, this construct has been empirically validated as an antecedent of customer loyalty with a new and wider scale (Kao et al, 2020;Torres et al, 2019). For the present study, we adopted Finn's (2005) measurement scale.…”
Section: Onboard Servicescapementioning
confidence: 99%